2022
DOI: 10.3920/bm2021.0101
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gut microbiome, organic acid profiles and viral antibody indexes of healthy Japanese with live Lacticaseibacillus detected in stool

Abstract: To estimate the health-promoting effects of Lacticaseibacillus paracasei (previously Lactobacillus casei) strain Shirota (LcS) that reached the lower gastrointestinal tract alive, we investigated the characteristics of gut microbiome, organic acid profiles, defecatory symptoms and serum viral antibody indexes of healthy Japanese adults between the group in whom live LcS was detected or not from stool. The β-diversity index of the gut microbiome constituted a significant difference between the live-LcS-detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Then, we analyzed the relationship between gut luminal succinate and intestinal flora in samples from human neonates and mouse pups. Our data indicated that there were significantly higher proportions of succinate-producing bacteria, including Enterococcaceae and Escherichia_Shigella ( Gradisteanu Pircalabioru et al., 2022 ), and significantly lower proportions of succinate-consuming bacteria, including Staphylococcaceae , Lactobacillaceae , Staphylococcus and Lactobacillus ( Shima et al., 2022 ) in human neonates with NEC than in control human neonates. Among the model mice, there were significantly higher proportions of succinate-producing bacteria, including Enterococcaceae , Clostridiaceae , Clostridium_sensu_stricto_1 , and Enterococcus ( Phuengjayaem et al., 2020 ) and significantly lower proportions of succinate-consuming bacteria including Lactobacillaceae and Lactobacillus ( Shima et al., 2022 ) in mice with NEC than in those without NEC.…”
Section: Discussionmentioning
confidence: 77%
“…Then, we analyzed the relationship between gut luminal succinate and intestinal flora in samples from human neonates and mouse pups. Our data indicated that there were significantly higher proportions of succinate-producing bacteria, including Enterococcaceae and Escherichia_Shigella ( Gradisteanu Pircalabioru et al., 2022 ), and significantly lower proportions of succinate-consuming bacteria, including Staphylococcaceae , Lactobacillaceae , Staphylococcus and Lactobacillus ( Shima et al., 2022 ) in human neonates with NEC than in control human neonates. Among the model mice, there were significantly higher proportions of succinate-producing bacteria, including Enterococcaceae , Clostridiaceae , Clostridium_sensu_stricto_1 , and Enterococcus ( Phuengjayaem et al., 2020 ) and significantly lower proportions of succinate-consuming bacteria including Lactobacillaceae and Lactobacillus ( Shima et al., 2022 ) in mice with NEC than in those without NEC.…”
Section: Discussionmentioning
confidence: 77%
“…In many individuals, lactate and formate were no longer detected at approximately 1 year of age. Lactate and formate are detected at a significantly low concentrations in adult feces [ 27 ]; therefore, their detection at relatively high concentrations for a certain period can be considered a characteristic of the organic acid composition of the gut during breast-fed infancy. An increase in propionate concentration was observed at around 8–12 months of age, followed by an increase in the butyrate concentration.…”
Section: Early Gut Microbiota Development and Changes In Organic Acid...mentioning
confidence: 99%